Maximization of near‐infrared modulation by optimizing the transparent conducting–electrode resistance - Han, Jisu; Lee, Sang Kyu; Park, Juhyun; Lee, Jugyeong; Ah, Chil Seong; Kim, Tae‐Youb (ETRI journal, 2025)
Traditional camouflage focuses on visual concealment, but the growing use of infrared (IR) detection systems has created a need for materials that can manipulate IR wavelengths. Electrochromic devices—commonly used for light and heat control—offer a promising solution for dynamic IR control. These systems rely on transparent conducting electrodes, with indium tin oxide (ITO) being the most common. However, ITO presents a challenge, as it generally blocks IR light transmissions. In this study, we optimize for IR transmissions by adjusting the ITO thickness, demonstrating excellent modulation in electrochromic devices. Devices with ITO thicknesses of 40 nm, 75 nm, and 302 nm are tested, with the 75‐nm electrode achieving 67.73% transmittance modulation in the visible range and 51.41% in the near‐infrared range. Response times for bleaching and coloration are 4.0 s and 2.8 s, respectively.